2018
DOI: 10.1038/s41598-018-32829-w
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule AgrA inhibitors F12 and F19 act as antivirulence agents against Gram-positive pathogens

Abstract: Small-molecule antivirulence agents represent a promising alternative or adjuvant to antibiotics. These compounds disarm pathogens of disease-causing toxins without killing them, thereby diminishing survival pressure to develop resistance. Here we show that the small-molecule antivirulence agents F12 and F19 block staphylococcal transcription factor AgrA from binding to its promoter. Consequently, toxin expression is inhibited, thus preventing host cell damage by Gram-positive pathogens. Broad spectrum efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 32 publications
(35 reference statements)
3
34
0
Order By: Relevance
“…Nevertheless, this observation was found to be in line with Yao et al (2006), who observed positive regulation of atlE in agr wild type. Also, Greenberg et al (2018) have noticed significant down regulation of atlE in MRSE upon treatment with an AgrA inhibitor F19 (biaryl hydroxyketones). These contradictory observations in atlE expression could be attributed to varied level of atlE transcription during various phases of bacterial growth cycle (Vuong et al, 2003; Batzilla et al, 2006; Mack et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, this observation was found to be in line with Yao et al (2006), who observed positive regulation of atlE in agr wild type. Also, Greenberg et al (2018) have noticed significant down regulation of atlE in MRSE upon treatment with an AgrA inhibitor F19 (biaryl hydroxyketones). These contradictory observations in atlE expression could be attributed to varied level of atlE transcription during various phases of bacterial growth cycle (Vuong et al, 2003; Batzilla et al, 2006; Mack et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Our results have important implications for the suggested application of quorum-sensing blockers for the treatment of S. aureus systemic infection. Such drugs have often been proposed and reported to have efficacy in local and occasionally systemic S. aureus infections [66][67][68]. An inherent problem with the interpretation of results achieved with quorum-sensing blockers is the frequently narrow window between genuine quorum-sensing blocking efficacy and bactericidal effects.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The impairing of AgrA functionality might perturb the agr operon transcription and consequently AIP production as well as agr -controlled virulence factors production. Several chemical compounds including 2-(4-methylphenyl)-1,3-thiazole-4-carboxylic acid, 9H-xanthene-9-carboxylic acid, 4-phenoxyphenol, savirin, ω-hydroxyemodin, biaryl hydroxyketones, and norlichexanthone appear to act by blocking the binding of AgrA to the agr operon promoters via direct interaction with the AgrA C-terminal DNA binding domain (Leonard et al, 2012; Sully et al, 2014; Daly et al, 2015; Baldry et al, 2016; Greenberg et al, 2018). Moreover, other compounds like naphthalene derivatives and biaryl compounds potentially could bind to the AgrA N-terminal phosphoryl-binding pocket, interfering with ArgA phosphorylation and binding to DNA (Khodaverdian et al, 2013).…”
Section: Inhibition Of Autoinducer Peptide Synthesismentioning
confidence: 99%
“…F-19 protected monocyte and macrophage cells from the lysis caused by several Gram-positive pathogens. Importantly, in an MRSA wound infection model, compound F-19 potentiated β-lactam and fluoroquinolone antibiotic activity, whereas in an MRSA bacteremia/sepsis model, F-19 alone and in combination with cephalothin protected the animals from a lethal infection with MRSA (Greenberg et al, 2018). In a previous study, F-12 and F-19 treatment increased the survival time of MRSA-infected larvae, as well as when they were used in combination with β-lactam antibiotics.…”
Section: Inhibition Of Autoinducer Peptide Synthesismentioning
confidence: 99%
See 1 more Smart Citation